1991
DOI: 10.1111/j.1600-0765.1991.tb01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human neutrophil functions by tetracyclines

Abstract: Tetracycline inhibition of neutrophil-associated collagenolysis has been the focus of a number of investigations. Evidence has suggested that this inhibition results from the ability of this family of antimicrobial drugs to bind divalent cations such as Ca2+ and Zn2+, two cations that are required for full expression of activity of metalloproteinases such as collagenase and gelatinase. Data presented in this study demonstrate that tetracyclines can also inhibit neutrophil-mediated RBC lysis, superoxide anion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 24 publications
1
83
1
1
Order By: Relevance
“…The possible mechanisms of doxycycline-induced MMPs inhibition include direct transcriptional inhibition because of blockage of the activating protein factor-1 (Hanemaaijer et al 1998), chelation of Zn 2+ or Ca 2+ thus blocking the active site of MMPs , or blockage of MT1-MMP-induced pro-MMP activation (Lee et al 2001). Previous studies showed doxycycline has effects on neutrophil suppression (Gabler and Creamer 1991), caspase 3 inhibition and suppression of microglial activation (Jantzie et al 2005). As MMPs inhibition might be only one of the possible neuroprotective mechanisms provided by doxycycline, we would like to choose a more specific MMPs inhibitor (GM6001) to further study the neuroprotective mechanisms and the long-term effects after MMP inhibition in neonatal HI brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms of doxycycline-induced MMPs inhibition include direct transcriptional inhibition because of blockage of the activating protein factor-1 (Hanemaaijer et al 1998), chelation of Zn 2+ or Ca 2+ thus blocking the active site of MMPs , or blockage of MT1-MMP-induced pro-MMP activation (Lee et al 2001). Previous studies showed doxycycline has effects on neutrophil suppression (Gabler and Creamer 1991), caspase 3 inhibition and suppression of microglial activation (Jantzie et al 2005). As MMPs inhibition might be only one of the possible neuroprotective mechanisms provided by doxycycline, we would like to choose a more specific MMPs inhibitor (GM6001) to further study the neuroprotective mechanisms and the long-term effects after MMP inhibition in neonatal HI brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline is a semisynthetic, longacting, second-generation tetracycline which is absorbed rapidly and penetrates well into the brain and CSF (48). Doxycycline has been shown to have anti-inflammatory effects that are separate and distinct from its antimicrobial action (13,16,35,43). These effects include the reduction of cytokine release and the inhibition of MMPs (7, 38).…”
mentioning
confidence: 99%
“…Algunos estudios han descrito, que a altas dosis el uso de doxiciclina puede bajar la tasa de filtración glomerular causando estados de isquemia en la arteriola eferente que puede llegar a inducir el incremento en los valores de creatinina sérica, una de las teorías es la reducción en el estrés oxidativo, disminuyendo los niveles de citoquinas e inhibición de la actividad de metaloproteinasas de matriz (5,30). Se ha determinado en diferentes estudios las propiedades antiinflamatorias e inmunomoduladoras de la doxiciclina asociadas a estos efectos (31,32).…”
Section: Ehrlichia Canis and The Effects Of Doxycycline In The Treatmentunclassified
“…One of the theories is the reduction of the oxidative stress, decreasing cytokine levels and inhibiting the activity of matrix metalloproteinases (5,30). The anti-inflammatory and immunomodulatory properties of doxycycline associated with these effects have been determined in different studies (31,32). …”
Section: Sistema Inmunementioning
confidence: 99%